Pengaruh depth jump exercise terhadap daya ledak otot tungkai pada pemain basket - Zulkarnaen, Imam Abusyahiqo; Rahim, Anita Faradilla; Rahmanto, Safun (Jurnal Sport Science, 2023)
Explosive power is the result of a combination of speed and strength exerted maximally in a quick and short time. Weakness in the explosive power of the leg muscles will cause disturbances in the stability of the body's balance, increasing the risk of falls, slipping and decreasing the athlete's jumping ability and performance. This research aims to determine the effect of depth jump exercise on leg muscle explosive power in basketball players in the city of Malang. This research is a quantitative research with a pre-experimental one group pre test post test approach and sampling using a purposive sampling method with a sample size of forty-five (n=45) in Merjosari Park, Malang City. The data obtained was in the form of lower leg muscle explosive power which was measured using the vertical jump test. This research obtained depth jump exercise results with a significance (p) of 0.000 (p<0.05). This research concludes that there is an influence of Depth Jump Exercise on the explosive power of leg muscles.